Ответы и объяснения

Лучший Ответ!
2012-05-02T18:35:27+04:00

2 уравнение умножить на (-2):

2х+у=-5         

-2х+6у=12

Складываем:

7у=7

у=1 тогда х=-6+3*1=-3

ответ:(-3;1)

 

2012-05-02T18:36:38+04:00

2x+y=-5

x-3y=-6

 

из №2 выражаешь х: х=-6+3у

подставляешь в 1: 2(3у-6) +у = -5

раскрываешь скобки: 6у-12+у=-5

                                   7у=7

                                   у=1

подставляешь в №2: х-3*1=-6

                                х=-6+3

                                 х=-3